Can proteomics contribute to biomonitoring of aquatic pollution? A critical review. (December 2020) - López-Pedrouso, M.; Varela, Z.; Franco, D.; Fernández, J.A.; Aboal, J.R.
Abstract: Aquatic pollution is one of the greatest environmental problems, and therefore its control represents one of the major challenges in this century. In recent years, proteomics has emerged as a powerful tool for searching protein biomarkers in the field of pollution biomonitoring. For biomonitoring marine contamination, there is a consensus that bivalves are preferred organisms to assess organic and inorganic pollutants. Thus, the bivalve proteome was intensively studied, particularly the mussel. It is well documented that heavy metal pollution and organic chemicals altered the structural proteins causing degradation of tissues of molluscs. Also, it is well known that proteins involved in stress oxidative such as glutathione and enzymes as catalase, superoxide dismutase or peroxisomes are overexpressed in response to contaminants. Additionally, using bivalves, other groups of proteins proposed as pollution biomarkers are the metabolic proteins. Even though other marine species are used to monitor the pollution, the presence of proteomic tools in these studies is scarce. Concerning freshwater pollution field, a great variety of animal species (fish and crustaceans) are used as biomonitors in proteomics studies compared to plants that are scarcely analysed. In fish species, proteins involved in stress oxidative such as heat shock family or proteins from lipid and carbohydrate metabolism were proposed as candidate biomarkers. On the contrary, for crustaceans there is a lack of proteomic studies individually assessing the contaminants. Novel scenarios, including emerging contaminants and new threats, will require proteomic technology for a systematic search of protein biomarkers and a greater knowledge at molecular level of those cellular pathways induced by contamination. Graphical abstract: Image 1 Highlights: Proteomics is a powerful tool in the quest for pollution biomarkers in biomonitors. Molluscs protein biomarkers are well studied in marine pollution. Structural, metabolic, stress oxidative proteins of marine bivalves as biomarkers. Fish protein biomarkers are most used in freshwater pollution. Emerging pollutants offers a new challenge for a proteomic approach.